The effect of remedial teaching on children with learning disabilities - Leary, P M; Arens, L J; du Plessis, J (South African medical journal, 1979)
A study of questionnaires completed by the parents and class teachers of 70 children with learning diabilities revealed evidence of considerable parental satisfaction with scholastic progress and improved behaviour. These advances were attended by a significant reduction in domestic tension and concern about the children's future. However, teacher ratings indicate that despite prolonged remedial teaching more than half of the group remained at a scholastic level below the average class performance.